Pengaruh Karakteristik Perusahaan Terhadap Modal Kerja Holding Ultra Mikro - Ratnasari Yahya, Dian; Elthaf Ilahiyah, Mar’a; Idayati, Farida (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2024)
This study aims to test and analyze the influence of company characteristics (financial leverage, operating cash flow, and company size) on working capital, as well as test and analyze the influence of company growth in moderating company characteristics (financial leverage, operating cash flow, and company size) on working capital. This research is a type of quantitative research, the sample used in the research uses a saturated sampling technique, where the sampling technique uses all members of the population as samples. So the number of samples used in this research is companies that are on the ultra-micro holding list, namely PT Bank Rakyat Indonesia (Persero) Tbk, PT Pegadaian (Persero) and PT Permodalan Nasional Madani (Persero). The research results show a significant influence between financial leverage (FL), operating cash flow (OCF), company size (size) on working capital. Company growth does not moderate company characteristics regarding working capital.